A DESCRIPTIVE STUDY OF DOCTRINES UNDER LAW OF CONTRACT - Dr. Itishree Mishra , Sidhartha Das (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Legally, a corporation is an autonomous legal entity with its members [Salmon v. Salmon and Co. A.C 22], Ltd. (1897). It is known as the "Veil of Integration." This definition is widely accepted as binding by courts. In this theory, the organization and its leaders have a fictitious cover. This is why the corporation seems to have a distinct personality of its members. However, in some cases , the court will perforate the case law and disregard the corporate veil in order to meet the individual behind the veil or to expose the true shape and essence of the undertaking in question. This article analyzes the principle "Veil of corporations," then discusses the phrase "Lifting the Corporate Veil" and then, with the aid of many examples, points out both the legal and legislative provisions for Lifting its Legal Veil.